Prison sexual abuse: Race, gender, and the rule of law - Buchanan, Kim (Columbia University, 2010)
In this dissertation, I argue that the exemption of prisons from the rule of law fosters abusive institutional practices that reveal the race and gender dynamics of sexual abuse in prison and in the outside world. The first article, Beyond Modesty: Privacy in Prison and the Risk of Sexual Abuse, shows that Fourth Amendment privacy offers little protection against the cross-gender searches and surveillance that expose women prisoners to sexual abuse by male guards. It proposes a reinterpretation of Fourth Amendment privacy that would recognize a constitutional right to be free from the fear, risk and reality of prison sexual abuse. The second article, Impunity: Sexual Abuse in Women's Prisons, shows that an edifice of constitutional, statutory and common-law rules confers near-complete institutional immunity against nearly all prisoner claims of custodial sexual abuse. These immunity rules parallel those of historical status regimes which excluded low-status litigants from courts on the basis of race and gender, such as civil death, slavery, segregation and the common law of marriage and rape--with similar results: low-status women of color are exposed to systematic and institutionalized sexual abuse, and are prevented from seeking protection or redress from the courts. The third article, Our Prisons, Ourselves: Race, Gender and the Rule of Law, develops these insights in men's prisons. In the absence of enforceable external rules, staff and administrators often adopt a gendered practice of institutional governance that requires prisoners to prove their manhood by fighting, and penalizes unmanly men by allowing others to rape them. These unlawful gendered practices are obscured by a false but powerful racialized narrative: most people inside and outside prison believe, inaccurately, that prison rape is mainly black-on-white. By casting sexual violence as a "complex and intractable" race relations problem for which administrators are not to blame, the racial narrative bolsters the rationale for exempting prison administration from the rule of law. Thus the perception (and reality) of unchecked prison violence supplies a reason for courts not to interfere with the unlawful institutional policies that foster it.
Keywords: approches et analyses; criminologie; discipline; droit; genre; intersectionnalité; mémoires/thèses; racisme; ressource en ligne; science politique et droit; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexuelles

Realizing the UN Declaration on the Rights of Indigenous Peoples: triumph, hope, and action - Joffe, Paul; Hartley, Jackie; Preston, Jennifer (Purich Pub., 2010)
Adopted by the UN General Assembly on 13 September 2007, the United Nations Declaration on the Rights of Indigenous Peoples affirms the “minimum standards for the survival, dignity and well-being of the indigenous peoples of the world.” The Declaration responds to past and ongoing injustices suffered by Indigenous peoples worldwide. It provides a strong foundation for improved relationships with states, and for the full recognition of the inherent rights of Indigenous peoples. Despite this, Canada was one of the few countries to oppose the Declaration. The contributors to this collection analyze the development of the Declaration, recall the triumph of its adoption, and illustrate the hopes and actions for its implementation. The discussion moves beyond Canadian borders to the international stage, providing accessible information and guidance on the Declaration and how it can be used to advance human rights. Policy makers, Indigenous communities, politicians, academics, lawyers, human rights advocates, NGOs, and anyone interested in the significance of the Declaration will find this to be a valuable resource. Contributors include Indigenous leaders, legal scholars and practitioners, state representatives, and representatives from NGOs, with extensive knowledge of and experience in Indigenous peoples’ human rights law, policy, and practice.
Keywords: 2000 à aujourd'hui; 2000-2009; ONU; amériques; approches et analyses; canada; capitalisme; cours; discipline; droit; droits des personnes autochtones; histoire et politique; justice sociale; pol4105; premier cycle; premiers peuples; premières nations; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences